COMPREHENSIVE GERIATRIC ASSESSMENT IN PRACTICE: WHAT DO PATIENTS SAY? - Tuğba Erdoğan; Birkan İlhan; Aslı Tufan Çinçin; Gülistan Bahat Öztürk; Mehmet Akif Karan (İstanbul Tıp Fakültesi Dergisi)
Objective: Comprehensive Geriatric Assessment (CGA) is one of the cornerstones of geriatric medicine. In this study, we aimed to find out how satisfied patients aged 60 and over with the application of CGA and whether they would express these complaints if geriatric-syndromes were not questioned. Materials and Methods: Patients who applied to the geriatric outpatient-clinic were included. An 18-question survey was applied by the geriatric nurse. The satisfaction and benefit expectations of the patients regarding both the application of CGA and specific sub-areas of CGA (urinary- fecal incontinence, falls, sleep, Mini-Nutritional-Assessment, Mini-Mental-State-Examination) were evaluated. They were asked whether they would express their complaints if these questions were not asked. Results: One-hundred-fifty patients were included in the study. The mean-age was 73.7±7 years. One-hundred-forty-eight patients were satisfied with the CGA and 139 of them thought it was beneficial. Seventy-three (49%) patients had urinary-incontinence, and 29 (19%) patients said that they would not report urinary-incontinence if this question had not been asked. Seventeen patients (11%) had fecal-incontinence and 16% of all patients said that they would not report fecal-incontinence if this question had not been asked. Twenty-nine of 85 patients stated that although they had a history of falling within the last year, they would not have stated this situation if this question was not asked. Ninety-three percent of the patients stated that they were satisfied with the Mini-Mental-State-Examination and that they thought this test would be beneficial for them. Conclusion: Although it takes time and is tiring, CGA is satisfactory for patients and enables the recognition of geriatric-syndromes that may remain hidden.